The mapping of Geography Courses at Universiti Pendidikan Sultan Idris with a standard curriculum for secondary school in Malaysia - Mohmadisa Hashim (Tanjong Malim, 2019)
The mapping of Geography Courses at Universiti Pendidikan Sultan Idris with a standard curriculum for secondary school in Malaysia by Mohmadisa Hashim